Komunikasi Interpersonal Pada Anak Autis Di Sekolah Luar Biasa (Slb) Autisma Bunda Bening Selakshahati - Syaffira Azzahra Nur Ridwan; Agus Aprianti (Syntax Idea)
Communication is a very important way of interacting to support social life in society. But communication will be difficult if there is interference. As for one of the disorders or difficulties in communicating as in children with autism. SLB Autism Bunda Bening Selakshahati is a special educational institution that can enforce verbal and non-verbal communication by means of interpersonal communication because communication occurs in two directions. In addition, it makes the development of autistic children not only able to carry out their needs for themselves, but also able to interact with other people. Interpersonal communication is carried out in order to convey messages properly with the aim that children with autism can know themselves and others, know the outside world, create and maintain more meaningful relationships, change attitudes and behavior, play and seek entertainment and can help other parties. in the process of communicating. This study aims to discuss the application of interpersonal communication in children with autism which includes supporting factors and inhibiting factors. The results showed the success in the implementation of interpersonal communication to children with autism.